Germplasm, Breeding, and Genomics in Potato Improvement of Biotic and Abiotic Stresses Tolerance - Tiwari, Jagesh Kumar; Buckseth, Tanuja; Zinta, Rasna; Bhatia, Nisha; Dalamu, Dalamu; Naik, Sharmistha; Poonia, Anuj K.; Kardile, Hemant B.; Challam, Clarissa; Singh, Rajesh K.; Luthra, Satish K.; Kumar, Vinod; et al. (Frontiers in Plant Science, 2022)
Potato is one of the most important food crops in the world. Late blight, viruses, and soil and tuber-borne diseases, insect-pests mainly aphids, whiteflies and potato tuber moth are the major biotic stresses affecting potato production. Potato is an irrigated and high fertilizers responsive crop, and therefore, heat, drought and nutrient stresses are the key abiotic stresses. The genus Solanum is a reservoir of genetic diversity, however, a little fraction of total diversity has been utilized in potato breeding. The conventional breeding has contributed significantly in development of potato varieties. In recent years, a tremendous progress has been achieved in the sequencing technologies from short-reads to long-reads sequence data, genomes of Solanum species (i.e. pan-genomics), bioinformatics and multi-omics platforms such as genomics, transcriptomics, proteomics, metabolomics, ionomics and phenomics. A much has been embarked upon the genome editing as a next-generation breeding tool. With the available high-throughput genotyping facilities and tetraploid allele calling softwares, genomic selection would be a reality in potato in near future. This mini-review covers an update on germplasm, breeding and genomics in potato improvement for biotic and abiotic stresses tolerance.